Assessing environmental impact of digital fabrication and reuse of constructive systems. (June 2021) - Kuzmenko, Kateryna; Roux, Charlotte; Feraille, Adelaide; Baverel, Olivier
Abstract: This paper presents a full life-cycle assessment study of a constructive system and addresses two following problematics: the impact of robotic fabrication and the performance of reuse solution for the end-of-life phase. As a case study a shell-nexorade hybrid constructive system is selected. The structure was designed computationally and fabricated robotically; a reuse scenario is developed for the end-of-life. The results point out an occurring of a significant impact transfer in system's life-cycle caused by robotic construction technology. Concretely, the contribution of the last can represent over 40% of the overall environmental impact of the structure in climate change category and exceeds the impact related to construction materials production in categories of toxicity and eutrophication. Regarding the end-of-life phase, a method for reuse assessment was developed and a strategy for control of an environmental performance of reclaimed structures is formulated. The data for environmental evaluation of digitally fabricated systems is provided.